Collagen binding integrins and cancer testis antigens in prostate cancer and melanoma - Pelo, Camilla (fi=Turun yliopisto|en=University of Turku|, 2016)
Camilla Pelo Collagen Binding Integrins and Cancer Testis Antigens in Prostate Cancer and Melanoma Department of Biochemistry, MediCity Research Laboratory, University of Turku, Finland Annales Universitatis Turkuensis, Painosalama Oy, Turku, Finland 2016 ABSTRACT Prostate cancer is the second most common cancer in men worldwide. The incidence of melanoma, in turn, is increasing faster than any other cancer incidences. In Finland, more than 5000 prostate cancer and 1200 new melanoma cases are diagnosed each year. One approach to further understand the cellular processes involved in prostate cancer and melanoma is to gain better knowledge about alterations in gene expression and their potential impact on the progression of the diseases. This thesis is focused on expression studies in two gene families; integrins and cancer testis antigens (CT antigens), in human prostate adenocarcinoma and advanced human melanoma. Integrins are heterodimeric transmembrane receptors which regulate many important cellular processes such as cell proliferation, migration and survival. CT antigens are frequently expressed in different types of cancers, but are only expressed in testis in healthy individuals. CT antigens are also highly immunogenic proteins. Due to the properties mentioned above, integrins and CT antigens can function as target molecules for the development of cancer diagnostics and drugs. One of the main purposes of this thesis was to study the expression of the four collagen binding integrins α1β1, α2β1, α10β1, α11β1 and the cancer testis antigen 16 (CT16) in cancer cell lines and human tissues of prostate cancer and metastatic melanoma. Additional aims included studies on the biological role of CT16 and the abundance of CT16 in sera of advanced melanoma patients. The prognostic and diagnostic significance of CT16 and the collagen binding integrins were also evaluated. Expression studies on collagen binding integrins and the CT antigen CT16 in melanoma and prostate cancer were limited and the biological role of CT16 was unknown. In this thesis, the expression levels of α2β1 and α11β1 were found to be significantly altered in prostate cancer tissues. Integrin α2β1 decreased gradually during disease progression while α11 was elevated in prostate carcinoma compared to healthy tissues. In advanced melanoma, enhanced levels of α2 were associated with a significant shorter overall survival in advanced melanoma. In this thesis, CT16 was identified as a frequently expressed melanoma CT antigen with an anti-apoptotic function. To conclude, this thesis presents α2β1 and CT16, as potential and promising biomarkers for advanced melanoma. This thesis reports also the first functional study of CT16. Keywords: Collagen binding integrins, α1β1, α2β1, α10β1, α11β1, Cancer Testis antigens, CT16, melanoma, prostate cancer, expression

Camilla Pelo Collagen Binding Integrins and Cancer Testis Antigens in Prostate Cancer and Melanoma Department of Biochemistry, MediCity Research Laboratory, University of Turku, Finland Annales Universitatis Turkuensis, Painosalama Oy, Turku, Finland 2016 TIIVISTELMÄ Eturauhassyöpä on toiseksi yleisin syöpä miehillä maailmanlaajuisesti. Melanoomatapausten lukumäärä lisääntyy muita syöpiä nopeammin. Suomessa todetaan yli 5000 uutta eturauhassyöpä- ja 1200 melanoomatapausta vuosittain. Tutkimalla geenien ilmenemismuutoksia ja muutosten mahdollisia vaikutuksia syövän etenemiseen voidaan ymmärtää solujen toimintaa. Tämän väitöskirjan tavoitteena oli selvittää integriinien ja syöpä/kives antigeenien (CT antigeenit, eng. Cancer Testis antigens) ilmentymistasoja eturauhassyövässä ja melanoomassa. Integriinit ovat heterodimeerisiä solukalvoreseptoreita, jotka säätelevät tärkeitä soluprosesseja, kuten solujen kasvua, erilaistumista ja migraatiota. CT antigeenit ovat immunogeenisiä proteiineja, jotka ilmentyvät eri syöpätyypeissä. Terveissä kudoksissa niiden ilmentyminen rajoittuu kiveksiin. Edellä mainittujen ominaisuuksien perusteella integriinit ja CT-antigeenit soveltuvat mahdollisesti kohdemolekyyleiksi syövän diagnostiikkaan ja lääkekehitykseen. Kollageenireseptori-integriinien α1β1, α2β1, α10β1 ja α11β1 ja syöpä/kives antigeenin CT16 ilmentymisestä melanoomassa ja eturauhassyövässä on saatavilla vain vähän tutkimustietoa. Tässä tutkimuksessa selvitettiin sekä kollageenireseptori-integriinien että CT16 antigeenin ilmentymistä ihmisen syöpäsolulinjoissa, ihmisen eturauhassyöpäkudoksissa ja metastaattisissa melanoomakudoksissa. Tavoitteena oli myös tutkia CT16 antigeenin biologista tehtävää ja sen ilmentymistasoa melanoomapotilaiden seerumeissa. Lisäksi arvioitiin CT16 antigeenin ja kollageeni-integriinien merkitys diagnostiikassa ja melanooman etenemisennusteessa. Tutkimuksessa α2β1 ja α11β1 integriinien ilmentymisen todettiin muuttuvan merkittävästi eturauhassyöpäkudoksissa. Integriini α2β1-ilmentymistaso väheni taudin etenemisen aikana ja integriini α11β1 määrä puolestaan havaittiin kohonneen eturauhassyövässä normaaliin kudokseen verrattuna. Kohonneet α2-ilmentymistasot metastaattisessa melanoomassa ennustivat potilaan lyhyempää elinaikaa syöpädiagnoosin jälkeen. CT16 antigeenin todettiin ilmentyvän runsaasti metastaattisessa melanoomassa ja CT16 antigeenillä havaittiin olevan antiapoptoottinen vaikutus soluihin. Tutkimuksessa esitellään α2β1 ja CT16 lupaavina melanoomabiomarkkereina. Tutkimus sisältää myös ensimmäisen toiminnallisen tutkimuksen CT16 antigeenistä. Avainsanat: Kollageenireseptori-integriini, α1β1, α2β1, α10β1, α11β1, syöpä/kives antigeeni, CT16, eturauhassyöpä, melanooma, ilmentyminen

Camilla Pelo Collagen Binding Integrins and Cancer Testis Antigens in Prostate Cancer and Melanoma Department of Biochemistry, MediCity Research Laboratory, University of Turku, Finland Annales Universitatis Turkuensis, Painosalama Oy, Turku, Finland 2016 SAMMANFATTNING Globalt sett är prostatacancer den näst vanligaste cancerformen hos män. Melanom, som är den mest elakartade hudcancern, är den cancerform som ökar snabbare än någon annan cancerform. I Finland diagnostiseras varje år mer än 5000 prostatacancerfall och 1200 melanomfall. Genom att erhålla bredare kunskap om genexpressionsförändringar och deras möjliga konsekvenser under cancerutvecklingen kan man utöka förståelsen för cellernas funktioner. Min avhandling fokuserar på integriner och cancer testikel antigener (CT antigener, eng. cancer testis antigens), samt deras expressionsnivåer och inverkan på prostatacancer och melanom. Integriner är heterodimeriska transmembranreceptorer som reglerar viktiga cellulära processer som celltillväxt, celldifferentiering och cellmigration. CT antigener är cancerspecifika och immunogena proteiner som expresseras i många olika cancertyper. Deras distribution i normala vävnader är främst begränsad till testiklar. På grund av dessa egenskaper är både integriner och CT antigener ideala för cancerforskning. Det huvudsakliga målet med min doktorsavhandling var att studera expressionsnivåerna av de kollagenbindande integrinerna α1β1, α2β1, α10β1 och α11β1 och CT16 i prostatacancer och melanom. I avhandlingen utvärderades också den prognostiska och diagnostiska signifikansen av de kollagenbindande integrinerna och CT antigenen CT16, och den biologiska rollen av CT16 studerades. För övrigt finns det få expressionsstudier av de kollagenbindande integrinerna och CT16 i prostatacancer och melanom. CT16:s biologiska roll är helt okänd. I denna avhandling noterades en signifikant α2- och α11-expressionsförändring i prostatacancer. Expressionsnivån av α2 minskade under prostatacancerns utveckling, och expressionsnivån av α11 var förhöjd i dåligt differentierade prostatacancervävnader jämfört med friska vävnader. Förhöjda α2-expressionsnivåer i de metastaserande melanomvävnaderna hos melanompatienter var förenade med en signifikant sämre livslängdsprognos efter cancerdiagnosen. I denna avhandling kunde man även presentera CT16 som en melanomantigen med anti-apoptotiska funktioner. CT16 och α2 kan också föreslås som specifika och lovande biomarkörer för metastaserande melanom. Avhandlingen presenterar också den första funktionella studien av CT16. Nyckelord: Kollagenbindande integriner, α1β1, α2β1, α10β1, α11β1, cancer testikel antigener, CT16, prostatacancer, melanom, expression